Study of RSA Algorithm: Integer Factorization Approach for secure Data Transmission - ,Shubhashree S. Savant, Nilesh K. Kajale (International Journal of Scientific Research and Management (IJSRM), 2017)
The Wired and wireless systems are the main technologies are implemented over the world as the technologies support easy datatransactions and transmissions. There is no technology can be stated which is fully provided with all areas of security measures. Each Systemhas its own loopholes and flaws. There is no existence of such systems which cannot be interrupted by Intruders. There may be securitymeasures applied by the technologies but at some states they can be broken by someone. In some situations system is easy to break and insome cases it takes lots of effort for an intruder to enter in the system. There may be an uncounted loss for a group or organizations if any oftheir important information is theft by the unauthorized persons or their enemies. To avoid all this losses due to data theft and accordingactivities there are many approaches presented by some inventors which can be used for better, efficient, and secure data transmissions overand after the networks. This paper is to state and provide information about one of the efficient and secured technique of data transmissioncalled RSA algorithm.